Guiana 1838 : the arrival - Jagessar, Rohit; Gaurav, Kumar; Bathija, Aarti; Williams, Neville; Rodney, Henry ([RBC Radio?], 2007)
Tells the story of East Indian immigrants who were brought to British Guiana to save a faltering sugar industry after the abolition of slavery.